Does Sales Promotion practices promote Customer Retention in the Oil Marketing Industry? A case of Goil Ghana Limited Dome-Kwabenya - Minua Ampofo, Gideon Kwaku; Yabani, Angela Akpene; Senadzo, Patrick (Journal of Research in Marketing (ISSN: 2292-9355), 2017)
The rationale behind this study was to establish whether sales promotion to any extent retains customers and to identity the perception of consumers on the benefits associated with sales promotion in the oil marketing industry. Staffs and customers of Goil Ghana Limited constituted the population of the study. A descriptive research design was employed and purposive and accidental sampling to select sixty-six (66) respondents. The result from the study discovered that sales promotion is capable of retaining customers in an oil marketing industry through sales promotional incentives. It was found that sales promotion encourages competition among oil and gas companies thereby compelling the players in the industry to provide quality service to customers resulting in a greater benefit for the consumer. This study concludes that if Goil Ghana Limited wants to enjoy good profits globally and Ghana in particular, it should work hard to increase customer retention through customer satisfaction and strong sales promotional activities.